Is Financial Reward Enough for Motivation in Football? - Vladimir Hrcek; Ivan Bagľas (Montenegrin Sports Academy and Faculty for Sport and Physical Education, 2018)
Motivation obviously plays a great role in the life of each athlete. The purpose of this paper is to bring out the importance of motivation in sport from the perspective of Self-determination theory (SDT). This theoretical review paper demonstrates the application of Self-determination theory (SDT) in amateur sports environment and professional athletes. Self-determination theory (SDT) postulates assumption that there is one motivational continuum rather than individual types of motivation and that each athlete has the same basic psychological needs that need to be satisfi ed. Our review is based not only on Self-determination theory (SDT) theory, but also on several studies from diff erent countries and environments. The review is focused on recommendations regarding implementation of specifi c strategies that could help athletes to improve their internal motivation in order to reach better performance and results.